READING COMPREHENSION IN UNIVERSITY STUDENTS FROM FOUR DIFFERENTIAL GEOGRAPHICAL AREAS OF THE COUNTRY - ROMANI MIRANDA, Dra. Úrsula Isabel (2023)
The present descriptive comparative research aims to determine the levels of reading comprehension in university students from different regions of the Perú. We worked with a sample of 256 first-year undergraduate students from four different geographical areas of the country (Lima, Callao, Huancayo and Iquitos). Likewise, an Ad hoc test (authors: Héctor Hugo Sánchez Carlessi and Úrsula Isabel Romani Miranda) of reading comprehension was applied to four texts, which presented one literal level question, two inferential or interpretive level questions and two critical-reflective questions evaluated digitally. The results were processed with the SPSS 26 program and it showed us that there are no significant differences in the four regions, regardless of whether they are national or private universities in terms of their reading comprehension levels. However, there are significant differences between the group made up of students from private universities and the group made up of students from public universities. Likewise, the test results show a significant difference with respect to the results of Text 1 and Text 4 where students from the private university group have a significantly higher score. Finally, a public university has higher scores in reading comprehension.